2021
DOI: 10.3892/etm.2021.11055
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin maintains MAPK7 expression and alleviates angiotensin II‑induced vascular endothelial cell inflammation and injury

Abstract: Statins have been reported to suppress vascular remodeling in rats with spontaneous hypertension. However, the possible effects of the statin pitavastatin on hypertension-induced endothelial inflammation and injury remain to be fully elucidated. The present study aimed to evaluate the effects of pitavastatin on HUVEC injury and inflammation. HUVECs were exposed to angiotensin (Ang) II with or without pitavastatin co-treatment, after which MAPK7 expression was detected via reverse transcription-quantitative PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Among the parameters that become different with sex, there is cell viability: in FHUVECs, there is a small but not significant decrease in cell viability, whereas in male cells, it is significantly increased. This is in line with previous HUVEC cell lines of unknown sex [51,52], but in the majority of cases, it was shown that Ang II induced viability loss in HUVEC cell lines of unknown sex (an exhaustive list of references about this point is reported in Table S3 [ [53][54][55][56][57][58][59][60][61][62][63][64][65][66]). The discrepancy could be attributed to the use of HUVEC cell lines versus the primary cultures we used, and to different methods of culture and viability determination.…”
Section: Discussionsupporting
confidence: 87%
“…Among the parameters that become different with sex, there is cell viability: in FHUVECs, there is a small but not significant decrease in cell viability, whereas in male cells, it is significantly increased. This is in line with previous HUVEC cell lines of unknown sex [51,52], but in the majority of cases, it was shown that Ang II induced viability loss in HUVEC cell lines of unknown sex (an exhaustive list of references about this point is reported in Table S3 [ [53][54][55][56][57][58][59][60][61][62][63][64][65][66]). The discrepancy could be attributed to the use of HUVEC cell lines versus the primary cultures we used, and to different methods of culture and viability determination.…”
Section: Discussionsupporting
confidence: 87%
“…Statins are not only applied for the therapeutics of cardiovascular diseases, but also for the treatment of neurological disorders ( Oesterle et al, 2017 ; Sanz-Cuesta and Saver, 2021 ), and lots of studies have suggested that statins have potential protective effects against sensorineural hearing loss ( Brand et al, 2011 ; Park et al, 2012 ; Fernandez et al, 2020 ; Whitlon, 2022 ). Pitavastatin (PTV) is a new-generation lipophilic statin that has been reported to exert anti-oxidative, anti-inflammatory, anti-neoplastic, and neuroprotective effects ( Kaneyuki et al, 2007 ; Gbelcová et al, 2017 ; Cui et al, 2018 ; Li and Liu, 2022 ), but the role of PTV in aminoglycoside-induced ototoxicity remains unknown.…”
Section: Introductionmentioning
confidence: 99%